Factors Affecting the Quality of Sleep in Patients with Chronic Obstructive Pulmonary Disease (COPD) - Titik Agustiyaningsih; Ririn Harini; Lilis Setyowati (Formosa Journal of Science and Technology, 2023)
COPD is a chronic disease characterized by airflow limitation in the respiratory tract. Symptoms that appear in COPD sufferers cause decreased sleep quality. This study aims to determine the factors that affect sleep quality in COPD patients. In the cross-sectional study design, the participants were 100 COPD sufferers without co-morbidities. Intake of non-probability sampling participants using purposive sampling method, the population of participants with COPD is domiciled in the working area of the Ciptomulyo Health Center in Malang. Data analysis used multiple logistic regression to determine the dominant factors in the sleep quality of COPD patients. The shortness of breath variable after being controlled by the smoking and coughing variable is a factor that greatly influences the sleep quality of COPD patients (OR=14).